Hydration of Calcium Sulfoaluminate-Based Binder Incorporating Red Mud and Silica Fume - Yubin Jun (Applied Sciences, 2019)
This study investigated the properties of hardened pastes made with calcium sulfoaluminate expansive agent (CSA), red mud, and silica fume. Five different ratios of 10:90, 20:80, 30:70, 40:60, and 50:50 were applied as the weight ratios of CSA and red mud. Red mud was replaced with 0, 5, and 10% silica fume by weight. Compressive strength, drying shrinkage, XRD, MIP, and SEM/EDS of the hardened pastes were performed. The results indicated that as the amount of CSA increased (i.e., as the amount of red mud decreased) up to 30%, sample strengths showed a tendency to increase. The main reaction product of the pastes was expansive ettringite, which was formed from the consumption of ye’elimite, anhydrite, gypsum, and Ca(OH)2. It was expected that C-S-H would be formed by the reaction of C2S in red mud; however, C-S-H phase was not present, and the pozzolanic activity due to the use of silica fume did not occur. The increase of CSA replacement level was effective for controlling the drying shrinkage of the samples. However, 50% replacement level of CSA induced excessive expansion, leading to the reduction in strength. It was found that the excessive expansion in the sample was reduced by the addition of silica fume.